2015
DOI: 10.1007/s00216-015-8635-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sample preparation and chromatographic separation for the parallel determination of taurine and edaravone in rat tissues using HILIC-MS/MS

Abstract: The quantitative analysis of taurine and edaravone in biological sample is critical in pharmaceutical studies. Although each of them can be individually analyzed by different approaches, concurrent quantification is still a highly challenging task with respect to their great polarity variation and the complex composition of tissue sample. In the present study, to simultaneously determine taurine and edaravone in rat tissue, the sample preparation and chromatographic separation conditions were evaluated and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The recovery cumulative excretion of edaravone after intravenous administration of 1 mg/kg in urine, bile, and feces were 0.30, 0.48, and 0.017%, respectively. According to Li et al [ 7 ], the peak concentration of edaravone in rat organ tissues (kidney, heart, brain, spleen, and liver) occurred at 30 min after the intravenous administration of 1 mg/kg edaravone and the highest concentrations of edaravone were detected in the kidney. In beagles, Shao et al [ 10 ] reported edaravone half-life of about 9 h and AUC 0–24h of about 26,694 ng/mL·h, 42,090 ng/mL·h, and 55,811 ng/mL·h after intravenous administration of 2.4, 4.8, and 9.6 mg/kg edaravone, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The recovery cumulative excretion of edaravone after intravenous administration of 1 mg/kg in urine, bile, and feces were 0.30, 0.48, and 0.017%, respectively. According to Li et al [ 7 ], the peak concentration of edaravone in rat organ tissues (kidney, heart, brain, spleen, and liver) occurred at 30 min after the intravenous administration of 1 mg/kg edaravone and the highest concentrations of edaravone were detected in the kidney. In beagles, Shao et al [ 10 ] reported edaravone half-life of about 9 h and AUC 0–24h of about 26,694 ng/mL·h, 42,090 ng/mL·h, and 55,811 ng/mL·h after intravenous administration of 2.4, 4.8, and 9.6 mg/kg edaravone, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The recovery cumulative excretion of edaravone after intravenous administration of 1 mg/kg in urine, bile, and feces were 0.30, 0.48, and 0.017%, respectively. According to Li et al [7], the peak concentration of edaravone in rat organ tissues (kidney, heart, brain, Comparable literature data showed that the half-life of elimination and the AUC after intravenous injection of 3.75 mg/kg edaravone in rats were 0.61 h and 8.76 µg/mL•h [5]. The recovery cumulative excretion of edaravone after intravenous administration of 1 mg/kg in urine, bile, and feces were 0.30, 0.48, and 0.017%, respectively.…”
Section: Distribution and Excretionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metformin and other biguanides (phenformin, buformin) were quantified by HILIC–ESI‐MS/MS in both live and postmortem forensic whole blood using a SeQuant ZIC HILIC column . Similarly, taurine and edaravone, a new combined therapy with commercial potential for treatment of stroke, were also determined by HILIC–ESI‐MS/MS using Atlantis HILIC silica column in rat tissues (kidney, heart, brain, spleen, and liver) simultaneously . Analysis of 2‐oxothiazolidine‐4‐carboxylic acid (OTZ), a cysteine prodrug, in simulated aqueous humour was developed according to FDA guidelines and finally gained well accurate and precise with LOD and LLOQ of 200 and 100 ng/mL.…”
Section: Chemical Drug Analysismentioning
confidence: 99%